Perancangan Sistem Pendataan Warga Berbasis Website Di Desa Rawa Bugel Bekasi - Najib, Akmal; Nuansyah, Bayu Dwimas; Faris, Muhammad; Muzakki, Muhammad Rafi; Wardian, Simon; Saputro, Sunu Febrian Eko; Kusdarnowo, Kusdarnowo; Sari, Rafika (Journal Of Computer Science Contributions (JUCOSCO), 2024)
Rawa Bugel Village, especially RW 10, still faces challenges in managing citizen data and information. Limitedfacilities and infrastructure because citizen data is still managed manually using Excel, often causing errors andinaccuracies in data, which in turn hampers the planning and implementation of development programs. awebsite-based citizen data collection system specially designed for Rawa Bugel Village. This system allows RW10 to manage population data and demographics. In addition, this system also gives citizens access to view andupdate their personal information. Therefore, designing a website-based citizen data collection system isimportant to improve data management and improve the quality of information available to the public. This systemadopts website technology to ensure easy access from various devices, including mobile devices that arecommonly owned by the public. The use of this website-based Citizen Registration System has made a positivecontribution to improving data management and information quality in Rawa Bugel Village.